Psychotherapie depressiver Störungen: Evidenz bei chronischer Depression und bei Komorbidität - Härter, Martin; Kühner, Christine; Schauenburg, Henning (Der Nervenarzt, 2018)
BackgroundPsychotherapy has been shown to be an effective treatment option for depressive disorders; however, its effectiveness varies depending on patient and therapist characteristics and the individual form of the depressive disorder.ObjectivesThe aim of this article is to present the current evidence for psychotherapeutic antidepressive treatments for patients with chronic and treatment-resistant depression as well as for patients with mental and somatic comorbidities.Material and methodsDuring the revision of the currently valid German S3- and National Disease Management Guideline (NDMG) on unipolar depression published in 2015, a comprehensive and systematic evidence search including psychotherapy for specific patient groups was conducted. The results of this search along with a systematic update are summarized.ResultsPsychotherapy has been shown to be effective in reducing depressive symptoms in patients suffering from chronic and treatment-resistant depression and in patients with mental and somatic comorbidities. The evidence is insufficient particularly for patients with mental comorbidities.ConclusionBased on the current evidence and clinical expertise the NDMG recommends psychotherapy alone or in combination with pharmacotherapy to treat most of these depressive patient groups. Evidence gaps were identified, which highlight the need for further research.
Gesehen am 20.08.2019